Commercialization of Microfinance in Cameroon : How can Microfinance Institutions manage their dual social and commercial goals? - Singhe, Steffi Sandra (Université de Nantes, 2020)
La commercialisation de la microfinance a mis au premier plan la performance financière des I MF, les IMF adoptant désormais une logique commerciale de rentabilité en plus de leur logique sociale établie de lutte contre la pauvreté. Cela pose un défi de gestion crucial pour les IMF pour équilibrer l'aspect social et commercial de leur mission. Cette thèse vise à analyser comment les IMF surmontent leurs défis pour atteindre leur double objectif social et commercial. Elle s'appuie sur le concept de bricolage comme perspective théorique et sur une approche méthodologique abductive, exploratoire et qualitative. La thèse vise également à fournir une meilleure compréhension du secteur de la microfinance camerounaise, en termes de son histoire et évolution, et des défis spécifiques au secteur. L'étude identifie diverses pratiques de bricolage que les IMF utilisent pour faire avancer la réalisation de leur double mission. Les résultats suggèrent l'utilisation de ces pratiques de bricolage par les IMF pour mobiliser des ressources, renforcer la légitimité et accroître leur ou/reach, dans un contexte caractérisé par des contraintes de ressources. Ces trois résultats de bricolage se renforcent mutuellement pour faciliter la réalisation du double objectif des IMF. Cette recherche a également mis en évidence les quatre phases d'évolution du secteur de la microfinance camerounaise et les cinq principaux défis auxquels sont confrontées les IMF du secteur. Cette thèse contribue à la littérature sur la microfinance. Elle propose un nouvel regard sur la gestion de la double mission des IMF en montrant comment les IMF mobilisent les stratégies de bricolage pour faire avancer leurs objectifs sociaux et commerciaux. Elle met en lumière le lien entre la littérature sur la microfinance et le bricolage. The commercialization of microfinance has brought to the forefront the financial performance of MF!s, with MF!s now adopting a commercial logic of profitability in addition to their established social logic of poverty alleviation. This poses a crucial management challenge for the MF!s in terms of balancing the social and commercial aspect of their mission. The main aim of this thesis is to understand how MFls overcome their challenges so as to achieve their dual social and commercial goals. lt draws on the bricolage concept as a theoretical perspective and on an abductive, exploratory and qualitative research approach. The thesis also aimed to provide a better understanding of the Cameroonian microfinance sector, in terms of its history and evolution, and the challenges specific to the sector. The study identifies various bricolage practices that the MF!s use to advance the fulfilment of their dual mission. The findings suggest the use of these bricolage practices by the MF!s to mobilize resources, build legitimacy, and increase outreach, in a context characterized by resource constraints. These three bricolage outcomes reinforce each other, and they all strengthen the achievement of the MF!s' dual goals. This research also highlighted the four phases of evolution of the Cameroonian microfinance sector and the five main challenges faced by MF!s in the sector. This thesis contributes to the microfinance literature. lt offers a new perspective on MF! dual-mission management by showing how MF!s mobilize bricolage practices to advance their dual social and commercial goals. lt brings light on the link between the literature on microfinance and bricolage.
Keywords: CSR; Cameroun; Microfinance; RSE; Responsabilité sociétale; Régulation (théorie)

Relationship between corporate social responsibility practice and its effects on the botton-line - Tandoh, Isaac; Aovare, Ayishetu (International Journal of Innovation and Scientific Research, 2020)
The study comparatively evaluates the relationship between Corporate Social Responsibility and Profitability in the fuel and gas sectors in Ghana. The descriptive survey design and quantitative methods was adopted to find a relationship between innovations in strategic stakeholder engagement with corporate profitability or bottom-line, with the mediating role of strategic stakeholder engagement leading to a firm’s bottom-line. An analysis of strategic stakeholder engagement and bottom-line of selected fuel and gas companies in the Kumasi Metropolitan, Asokore Mampong, Oforikrom and Ejisu Municipalities was provided.A five point closed ended Likert Scale self-administrable structured questionnaire and researcher guide to aid participants answer relevant questions was used to confirm that innovations in strategic stakeholder engagement fueled increases in corporate bottom-line of selected companies. The four major steps of analysing data collected from Atkinson’s (2002) categories of quantitative data analysis was used, following which the primary data/information gathered and coded was analysed using the Statistical Package for Social Sciences to guarantee validity and reliability of the various investigations conducted. The hierarchical multiple regression of the Baron and Kenny’s (1986) procedure was also adopted to analyse for study the mediating effect of innovation on the relationship between strategic stakeholder engagement and corporate bottom-line.The study opines the involvement of key stakeholder participation in the siting and general operations of fuel and gas companies given the divergent viewpoints of operators and stakeholders (O’Riordan, 2017). A discovery of a statistically significant positive influence of perceptions of CSR towards customers on an organization’s image in general intensifies the suggestion that mangers of fuel and gas sectors take special interest in innovative ways of engaging strategic stakeholders due to its influence and ripple mediating effect on corporate bottom-line to improve the performance of the business or induces increases in profit.
Keywords: Brand; Corporate Social Responsibility; Employees; Image; Perception; Strategic Stakeholder

The Impact of Employee Board Representation on the Firm’s CSR Engagement : evidence from the French Context - Boukadhaba, Amal (Le Mans Université, 2020)
Cette thèse propose d’examiner la relation entre la représentation des salariés dans le conseil d’administration et l’engagement RSE de l’entreprise. En particulier, nous étudions comment les investisseurs perçoivent-ils le reporting RSE et laperformance ESG lorsque les salariés sont représentés au sein du conseil d’administration. En utilisant un échantillon de sociétés françaises appartenant à l’indice SBF 120 sur deux périodesdifférentes de 2001 à 2011 et de 2007 à 2017, nos résultats montrent que la présence des administrateurs salariés modère positivement la perception du reporting RSE et négativement la perception de la performance ESG par les investisseurs. Un examin plus détaillé montre que les administrateurs élus par les salariés par leur droit de travail améliorent exclusivement la performance sociale et modèrent négativement la perception des investisseurs vis-à-vis de la performance ESG. Au contraire, les administrateurs élus par les salariés actionnaires renforcent la performance ESG globale ainsi que les performances environnementale et de gouvernance et modèrent positivement la perception de la performance ESG par les investisseurs. Nos résultats mettent en évidence un conflit d’intérêts entre les actionnaires et les administrateurs salariés, notamment avec les représentants des travailleurs. Cette thèse couvre plusieurs disciplines à savoir la comptabilité, la gouvernance d’entreprise et lagestion des ressources humaines. En conséquence, elle intérèsse vivement les législateurs, les investisseurs, les managers et les actionnaires.
Keywords: Actionnariat du personnel; Administrateurs salariés; CSR reporting; ESG performance; Employee board representation; Firm market value; Gouvernement d'entreprise; Performance ESG; Performance boursière; Personnel -- Participation à la gestion; Relations avec les actionnaires; Reporting RSE; Responsabilité environnementale; Responsabilité sociétale; Sociétés

Corporate Social Responsibility and Organizational Performance of Oil Companies in Southern Nigeria - Daubry, Powei Martin (Walden University, 2020)
In this study, the relationship between corporate social responsibility (CSR) activities and organizational performance (OP) of international oil companies (IOCs) operating within the Niger Delta Region of Nigeria was investigated. Grounded on the stakeholder theory, the problem being investigated involved the extent to which dimensions of CSR in terms of centrality, visibility, and voluntary contributions impact measures of OP (relational capital and employees’ commitment) specifically within the oil industry in Nigeria. Data for the study were obtained through a quantitative survey instrument from a sample of a population of individuals (N=270) living in host communities who are impacted by IOC activities in Rivers, Delta, and Bayelsa States. The results of the multiple regression analysis indicated a predictive model F (1, 268) = 774, p < 0.05, and R 2 = .742, which indicated that CSR was positively and significantly correlated with OP. In addition, centrality and voluntary contributions significantly affected OP. Also, centrality and voluntary contributions significantly correlated with employees’ commitment while only voluntary contributions significantly correlated with relational capital. The results of the study corroborated the need for CSR practitioners in the oil industry within the Niger Delta to operate in a socially responsible manner. The implications for positive social change include the potential for policy makers to use the findings to create mutually beneficial relationships that could contribute to resolving persistent adverse issues involving oil exploration and production in the Niger Delta Region by improving the socioeconomic dynamics of the host population, not only in the region, but also throughout Nigeria and similar countries.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Oil companies; Organizational performance

Corporate social responsibility and executive personality - Li, Xin (Simon Fraser University, 2020)
My dissertation investigates two streams of managerial accounting literature; specifically, corporate social responsibility (CSR) and executive personality. Paper 1 focuses on whether companies strategically engage in CSR practices to retain employees. Using a difference-in-differences design, I find that an increase in the enforcement of non compete agreements (which enhances a firm’s ability to retain employees) deteriorates CSR performance. Paper 2 extends prior literature and links managerial risk tolerance and firms’ CSR performance. The empirical result of Paper 2 shows that pilot CEOs are less likely to exhibit better CSR performance. Paper 3 examines the spillover effect of managerial risk tolerance along the supply chain. Specifically, I follow Paper 2 to use the pilot status of CEOs to proxy for the customers’ risk tolerance level. Overall, the results support a negative association between customer risk tolerance and supplier investment efficiency, and customer companies ran by pilot CEOs leads to supplier investment inefficiency. Each chapter is designed to be self-contained and provides a more detailed discussion of the research question and contribution.
Keywords: CEO; CSR performance; Corporate Social Responsibility; Non-compete enforceability; Pilot; RSE; Risk tolerance; Supplier investment efficiency

The Trajectory of Illicit Waste Trade in Africa: Implications for Human Rights and Sustainable Development - Umenze, Nnamdi Stanislaus (Journal of Law, Society and Development, 2020)
As globalisation intensifies, the environmental burden of economic development is being shifted to poor countries. This development manifests in waste trade involving the transboundary shipment of toxic waste from developed to developing countries. This article evaluates the strategies with which waste trade is being perpetuated to the detriment of sustainable development and human rights values in Sub-Sahara Africa. It argues that capitalism has influenced massive generation and commodification of waste, especially in industrialised countries. It has also established that globalisation has made the transboundary shipment of waste easy. Moreover, foreign investments in the waste industry in developing countries appear to be a means by developed countries to perpetuate waste shipment to developing countries, which helps waste traders to avoid stringent regulations and high costs of waste management in developed countries. Therefore, such investments in developing countries should not always be viewed as a breakthrough in attracting foreign investments. The findings made include that despite the existence of the Basel and Bamako Conventions at global and regional levels, respectively, waste trade has continued in different forms in Africa, where waste merchants exploit the low-cost facilities, cheap labour and weak regulatory frameworks. The trend includes the reckless dumping of hazardous industrial waste, electronic waste as well as ostensible investment in “dirty industries” in some African countries. It concludes by urging the states to individually establish robust mechanisms that protect the environment and enforce environmental rights. These measures will help complement the collective efforts they have made in multilateral and regional agreements.
Keywords: Africa; electronic waste; globalisation; human rights; sustainable development; toxic waste trade